Etika dan Keterbukaan Informasi: Bagaimana Aparat Desa Memahami Tanggung Jawab Akuntansi - Fardhan M Nur Poloalo; Andriyawan E. Karim; Harun Blongkod (JEMSI (Jurnal Ekonomi, Manajemen, dan Akuntansi), 2026)
This article examines the role of ethics and information disclosure in village accounting management, focusing on how village officials understand and carry out accounting responsibilities. Using a Systematic Literature Review (SLR) approach, this research examines various studies related to accounting ethics, public transparency, and village financial governance. The research findings indicate that although the regulatory framework imposes requirements for transparency and accountability, there is a significant gap between prescriptive regulations and their practical implementation in real-world scenarios. Village officials' understanding of accounting ethics remains variable, while the implementation of information disclosure is often limited to administrative fulfillment, rather than as a moral value in public service. This article emphasizes the need to strengthen capacity, ethical understanding, and an organizational culture that supports transparency to improve the quality of village accounting governance.